Teknik Keamanan Data Menggunakan Vigenere Cipher Dan Electronic Code Book (ECB) - Widarma, Adi; Siregar, Helmi Fauzi; Irawan, M Dedi (STIKOM Tunas Bangsa Pematangsiantar, 2019)
Data is important information both personal, group and company. Because of the importance of the data, many parties have kept the data very confidential so that it is not publicly recognized. But it cannot be denied that data can be stolen by unauthorized people. Request the data to be unsafe. A technique is needed to move data, namely by using cryptography. One of the existing cryptography techniques is classical cryptography such as vigenere cipher. However, this classic has a low level of security so it needs to be upgraded again. Then a combination of cryptography algorithms using modern cryptography, Electronic Code Book (ECB) is carried out. Using a combination of these two algorithms will improve data security.